REVITALISASI MUTU PRODUK EKSPOR MELALUI PENDAMPINGAN INOVASI DESAIN PRODUK DAN HKI PATUNG TERRAZZO DI BANTUL YOGYAKARTA - Moh. Rusnoto Susanto; Sri Wastiwi Setiawati; Anggit Dwi Hartanto (LPPM IST AKPRIND Yogyakarta, 2018)
The potential of creative industry business in Yogyakarta is very fast and very wide open for business actors, especially business actors of handicraft industry through business activities that focus on creation and innovation. Especially the terrazzo sculpture industry in Guwosari and Kasihan, Bantul in production and export activities as a strategic social and cultural capital development effort. This is necessary given the tight competitiveness of global markets and as a strategic effort to prepare the competitiveness of both Partners in the role of the ASEAN Economic Community (MEA) which requires specific qualifications. Methodology undertaken through mentoring and development of Partners (HR, Governance, and Innovation of Product Design and HKI Potential) through technology transfer. Assistance conducted regularly and regularly that has been done in year II includes; advanced facilitation of studio management system (workshop), innovation of product design, updating of e-Commerce content, International Jogja International Furniture & Craft Fair Indonesia (JIFFINA) 2017 exhibition at JEC, Jogjakarta Street Sculpture Project (JSSP) exhibition, and HKI Regulations on products flagship UKM Terrazzo Sculpture and Stone at PT. Amartha Indotama di Guwosari Pajangan, Bantul and Komharo Studio, Kasihan Bantul. The results of this mentoring activities are in line with the objectives of the PPE Program of Kemenristek Dikti to provide assistance in solving Partners problems to improve the quality of export products, production volume, and HKI protection for the acquisition of Copyright Certification. Then pioneered a representative e-commerce network both design and content to enhance global marketing network with more effective, efficient, and independent export management.